Os Santos d'Afurada: arte, devoção e comunidade: dimensão artística, devocional e antropológica - Oliveira, Cátia (2022)
This paper is a reflection on a set of ten images and a Via Sacra conceived by the sculptor Altino Maia (1911-1988), between 1955 and 1957, for the new parish church of São Pedro da Afurada (Vila Nova de Gaia). The study addresses the images in several dimensions: artistic and iconographic, including ordering processes and creation; the anthropological, detailing the community's reception and reaction to these sculptures. Nine of the images were «hidden» in cabinets for long years, removed from the eyes of the faithful, received the popular and derogatory names of «Santos Pretos» or «Santos das Rodilhas» and were even victims of aggression attempts. The sculpture of the Crucified Christ was exhibited on the apse's back wall until 2021 and the Via Sacra continues to be displayed on the north wall of the parish church of São Pedro da Afurada. Based on the documentary and visual sources of the time and the testimony of some inhabitants of Afurada, this paper intends to analyze the circumstances of commissioning and artistic creation, developing an iconographic study of the images, contextualizing them in their time and to understand these object-images (in line with Jérôme Baschet) from an anthropological perspective.